Essays in Indian art, religion, and society : vol. 1 - Shrimali, Krishna Mohan, 1947- (New Delhi : Munshiram Manoharlal Publishers, 1987)
Articles culled from the proceedings of the Indian History Congress, 1935-1986.
Includes bibliographies.
Keywords: India -- Civilization